Nano-geometric deformation and synergistic Co nanoparticles—Co-N4 composite sites for proton exchange membrane fuel cells. Issue 11 (4th October 2021) - Cheng, Xiaoyang; Yang, Jian; Yan, Wei; Han, Yu; Qu, Ximing; Yin, Shuhu; Chen, Chi; Ji, Ruiyi; Li, Yanrong; Li, Guang; Li, Gen; Jiang, Yanxia; et al.
Abstract : Co single-atom (CoSA ) catalysts of the CoN4 moiety usually show an unsatisfactory oxygen reduction reaction (ORR) activity due to poor O2 activation. Abstract : Co single-atom (CoSA ) catalysts of the CoN4 moiety usually show an unsatisfactory oxygen reduction reaction (ORR) activity due to poor O2 activation. Herein, we open up a novel strategy to improve the ORR activity of the CoSA –N–C catalyst. Its structure was first built to involve the deformed CoN4 site and enhance mesoporosity. Secondly, Co nanoparticle and CoN4 (CoNP –CoN4 ) composite sites were created in the catalyst and the total CoN4 density was effectively replenished. Finally, the concave nanocube-like catalyst showed an excellent ORR performance in the RDE test ( E 1/2 = 0.83 V vs. RHE, 12 mV loss after 50K cycles) in acidic media. Furthermore, the catalyst showed a high power density in the fuel cell test ( P max -H2 –O2 ca. 1.207 W cm −2 ). Theoretical studies agree with experimental findings that both CoNP –CoN4 composite sites and deformed CoN4 can enhance O2 activation. In addition, the inhibited H2 O2 formation and the enhanced adsorption of radical oxygen species due to CoNP –CoN4 composite sites can greatly reduce carbon layer erosion, resulting in improved performance in both activity and durability. Our finding not only provides a novel strategy to develop ORR catalyst but also brings new insights into ORR fundamentals.